Possible mechanism for mianserin induced neutropenia associated with saturable elimination kinetics. Issue 6506 (16th November 1985) - O'Donnell, J L; Sharman, J R; Begg, E J; Colls, B M; Moller, P W
Abstract : Two cases of mianserin induced neutropenia associated with prolonged elimination of the drug were studied. In each case the pharmacokinetic profile suggested saturable elimination kinetics, and the temporal relation of mianserin concentrations and the neutrophil count suggested a direct toxic effect of mianserin on the bone marrow. Until further studies are carried out the plasma mianserin concentration and neutrophil count should be measured in any patient who develops an infection while taking this drug.